Virtual-reality exergaming improves performance during high-intensity interval training - Farrow, M.; Lutteroth, C.; Rouse, P. C.; Bilzon, J. L. (European Journal of Sport Science, 2019)
Purpose: To determine if: (i) mean power output and enjoyment of high-intensity interval training (HIIT) are enhanced by virtual-reality (VR)-exergaming (track mode) compared to standard ergometry (blank mode), (ii) if mean power output of HIIT can be increased by allowing participants to race against their own performance (ghost mode) or by increasing the resistance (hard mode), without compromising exercise enjoyment.